Comunicação organizacional: implicações da comunicação downward e do feedback no engagment - Sampayo, Marta Mello (2012)
This article aims to contribute to understanding the impacts of organizational communication in terms of quality of downward information, communication channels and feedback on work engagement. The literature reveals that the mobilization of employees through a greater involvement with the organization and the work contributes to a better organizational and individual performance. One way of achieving this mobilization is achieved by improving communication, making it easier for employees to understand the objectives of the organization and believe in their contribution to reach them. In this context this article focuses on the existing literature in this area and contributes to an understanding of downward communication and feedback emphasizing its effects on organizational involvement (voice) and promoting a greater connection to the organization and employees to work (engagement). This is of particular relevance since the implementation of research in this area will allow the implementation of programs to improve communication with impact for organizations and individuals to improve their performance and quality of life.